Policy Evaluation of Regional Leading Sports Guidance and Development in Kuningan: Case Study Athletic - Nanang Mulyana; Yudha Munajat Saputra; Amung Ma'mun; Yunyun Yudiana (JUARA : Jurnal Olahraga, 2023)
This study evaluates the Policy for Coaching and Development of leading sports branches in Kuningan Regency. This study aimed to determine financial support, policy structure for leading sports, talent identification systems, future support for athletes, training facilities, improving human resources for trainers, national and international competitions, and research on the development of leading sports. The method used in this research is to use qualitative methods. The participants in this study were the Kuningan Regency Disporapar, KONI Kuningan Regency, and PASI Kuningan Regency. The instruments in the study used document review guidelines, interview guidelines, observation guidelines, and questionnaires. The data collection process is carried out through the stages of preparation, implementation, review, and evaluation. The data processing steps start with document review, interviews, verification, and validation. The results of this study show that the financial and structural support for leading sports is good, the system for recruiting leading athletes and training facilities still needs to be improved, and the improvement of human resources for trainers and competition calendars is good. Still, there needs to be research on leading sports in Kuningan Regency.